Study on Performance of Cabin Air filters Under Different Work Conditions. Issue 2 (April 2021) - Wei, Shuhong; He, Yongao; Yin, Wei; Tian, Cheng; Jiao, Pengfei; Bian, Jiachen
Abstract: The in-vehicle air quality has increasingly attracted the attention of people. Hence, air filter performance under actual work conditions demonstrates remarkable significance. It is verified that the electrostatic adsorption can dramatically enhance the fractional efficiency of small-particle pollutants without increasing the pressure loss; as regard a lack of fractional efficiency test on the filter during the whole life cycle in current standards, the paper studied the tendency of filter's fractional efficiency variation in the whole life cycle and discovered that fractional efficiency of small particles decreased first after increase due to the shielding of electrostatic charge; the tests on different air speed and area of filtered paper were carried out, showing that increasing the area of filtered paper can significantly lower the pressure loss and increase the filtration efficiency, which is of vital significance to provide the reference for further improving the performance of cabin air filter.